A controlled clinical study of the effects of the Ni-Ti Memoria® Leaf Spring Activated Expander - Manzella Kevin S.; Warunek Stephen; Conley R. Scott; Al-Jewair Thikriat (Sciendo, 2018)
To evaluate the dental effects of the Ni-Ti Memoria® Leaf Spring Activated Expander (MLSAE) in adolescent orthodontic patients presenting with maxillary transverse constriction.